1990
DOI: 10.4319/lo.1990.35.6.1221
|View full text |Cite
|
Sign up to set email alerts
|

An investigation ofhydrogen peroxide chemistry in surface waters of Vineyard Sound with H218O2 and 18O2

Abstract: Abstract180-labeled H,O, and 0, have been used to determine absolute rates and pathways of peroxide formation and decay processes in surface waters of a coastal marine site. Reactions were followed by incubating seawater samples with '*O, or H, l8O, and following the chemical transformation of the isotope label.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 11 publications
6
102
2
Order By: Relevance
“…Our observed H 2 O 2 half-life in unfiltered Chesapeake Bay surface waters is in good agreement with determinations by Cooper et al (1994). For Bay waters, t 1/2 ranged from 2.49 to 12.2 h. The latter is similar to the 12.6 h half-life for unfiltered Vineyard sound surface waters observed by Moffett and Zafiriou (1990). Loss of MHP in surface waters is faster by nearly a factor of 3.…”
Section: Sample Stability Studiessupporting
confidence: 78%
“…Our observed H 2 O 2 half-life in unfiltered Chesapeake Bay surface waters is in good agreement with determinations by Cooper et al (1994). For Bay waters, t 1/2 ranged from 2.49 to 12.2 h. The latter is similar to the 12.6 h half-life for unfiltered Vineyard sound surface waters observed by Moffett and Zafiriou (1990). Loss of MHP in surface waters is faster by nearly a factor of 3.…”
Section: Sample Stability Studiessupporting
confidence: 78%
“…Gerringa et al (2004) calculated a net production rate of 7 nmol L −1 h −1 at irradiance levels of 2.8 (UVB), 43 (UVA) and 346 W m −2 (VIS/PAR) in 0.2 µm filtered water from the eastern Atlantic close to the Equator. These low rates are presumably due to lower DOC concentrations and higher decay rates due to colloids or enzymatic activity in natural waters (Moffett and Zafiriou, 1990;Petasne and Zika, 1997). Given that H 2 O 2 plays an important role in the Fe redox-chemistry, our experiments suggest that PS may have a significant indirect effect on Fe redox-speciation due to the enhanced photochemical production of H 2 O 2 .…”
Section: Numerical Modelmentioning
confidence: 87%
“…This ddark decay lifetimeT of H 2 O 2 can vary from hours to weeks in the ocean (Petasne and Zika, 1997), but typically may be around 4 days in the open ocean (Plane et al, 1987). Filtration of seawater to remove the biota typically results in a dramatic reduction in the decay rate of H 2 O 2 (Moffett and Zafiriou, 1990;Petasne and Zika, 1997). Isotopic studies of the decomposition of H 2 O 2 have found that 65-80% of the decay was from catalase activity (reduction to H 2 O and O 2 ) with 20-35% from peroxidase activity (reduction to H 2 O only) (Moffett and Zafiriou, 1990).…”
Section: Redox Cycling Of Iron In Seawatermentioning
confidence: 99%
“…Filtration of seawater to remove the biota typically results in a dramatic reduction in the decay rate of H 2 O 2 (Moffett and Zafiriou, 1990;Petasne and Zika, 1997). Isotopic studies of the decomposition of H 2 O 2 have found that 65-80% of the decay was from catalase activity (reduction to H 2 O and O 2 ) with 20-35% from peroxidase activity (reduction to H 2 O only) (Moffett and Zafiriou, 1990). The amount of colloidal material has also been shown to influence the decay rate of H 2 O 2 (Yuan and Shiller, 2001).…”
Section: Redox Cycling Of Iron In Seawatermentioning
confidence: 99%